A first qualitative and quantitative study of marine cave fish assemblages of intracave cavities. (5th December 2021) - Kovačić, M.; Glavičić, I.; Paliska, D.; Valić, Z.
Abstract: This study aims to describe for the first time the diversity and abundance of "cave within cave" fish species assemblage and to study the effects of habitat variables on these assemblage patterns. The term "cave within cave" is used to describe small, enclosed cavities and other enclosed spaces regularly present on the inner surface of large marine caves. The quantitative study was conducted from October to November 2019, in a large marine cave under Lučice Bay, on the south side of Brač Island in the eastern Adriatic Sea. In total 48 one-square-meter surface squares were sampled, extending 40m inside from the cave entrance, and down to a depth of 26m. A total of 18 fish species were found in the studied cave, of which 15 were recorded on the square frames. Nine species were found in intracave cavities, including five species which occurred exclusively in this highly cryptic habitat. The three strictly "cave within cave" fish species ( Corcyrogobius liechtensteini, Didogobius splechtnai and Zebrus zebrus ) prevailed by abundance and by frequency of occurrence over other twelve species recorded on the squares. The total fish abundance significantly increased with increased light intensity, with steeper surface and from the bottom to the top of the cave, while the total biomass and species richness significantly increased only with the increased light intensity. The assemblage structure of "cave within cave" fishes differed significantly with light intensity, among different surface inclinations and among different cave positions. The "cave within cave" fish species differ in habitat preferences, some species inhabit the entrance of the cave with high light conditions and rich zoocover, and others inhabit further inside the cave with low light conditions. Highlights: The "cave within cave" fishes, an unstudied marine cave ichthyofauna, highly contributed to cave fish species richness. The "cave within cave" fishes were abundant, with recorded maximum of 12 individuals per square meter and average of about 3.5 individuals per square meter. The abundance, biomass and species richness of "cave within cave" fishes reach higher values close to the entrance and decrease with increased distance from it. The fish assemblage structure differed significantly with light intensity, among different surface inclinations and among different cave positions.